Flow patterns, hotspots, and connectivity of land-derived substances at the sea surface of Curaçao in the southern Caribbean - V. Bertoncelj; V. Bertoncelj; F. Mienis; P. Stocchi; P. Stocchi; E. van Sebille (Ocean Science)
The southern Caribbean Island of Curaçao is abundant in coral reef communities, but they are declining. Land-derived nutrients and pollutants are a potential contributing factor to this decline, since these substances, after entering the ocean, can be transported towards reef sites by ocean currents. To study the movement of the substances and their potential impact on coral reefs, we developed the model SCARIBOS (South CARIBbean Ocean System), with a 1/100°<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="37pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="938fe0892e19f21ebc40b0a1e90adc69"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="os-21-945-2025-ie00001.svg" width="37pt" height="14pt" src="os-21-945-2025-ie00001.png"/></svg:svg> resolution, covering the period from April 2020 to March 2024 (excluding spin-up time) to analyse flow patterns within that period in close proximity to Curaçao. SCARIBOS is used as hydrodynamic input for Lagrangian particle tracking analysis with the Parcels framework, where we assess the distribution of positively buoyant substances and explore connectivity within Curaçao's coastlines as well as with the nearby regions of Aruba, Bonaire, the Venezuelan islands, and a portion of the Venezuelan mainland. Results reveal two dominant processes: the northwest-directed Caribbean Current and weaker cyclonic eddies moving in the opposite direction. These flow patterns influence hotspot locations, with higher accumulation of positively buoyant substances occurring during eddy events. Our analysis also highlights increased particle accumulation of land-derived substances in the northwest of Curaçao, corresponding to the prevailing currents. While the focus is on land-derived nutrients and pollutants, this methodology can be extended to study other particle types such as plastic debris and coral larvae, providing valuable insights for marine conservation efforts and environmental management.